Personality Traits and Misdemeanor of Adolescents in a Catholic High School - Sombero, Josefa Darling G.; Maravilla, Ma. Wilma M. (Philippine Social Science Journal, 2020)
Distinctive personality traits account for every person, who they are, and how they behave. These have impacts on the way people perceive the world. Like adults, children and adolescents can be described in terms of personality traits such as characteristics, patterns of thinking, feeling, and behaving. This study reports the personality traits and extent of a misdemeanor of high school students. Also, it seeks to find out if one’s personality traits affect the behavioral tendencies and vice-versa, how these traits develop across childhood and adolescence, and how they relate in the transition of adolescence period that involves changes in biological, socio-emotional, and well-being. The vast majority of research has focused more on adulthood and is scarcer than adolescent personality traits research. Additionally, the relationship between personality traits and misdemeanor and the demographic variables was also explored.